Il difficile equilibrio fra etica e libertà nella ricerca: Dilemmi etici, conflitti e strategie - Crivellaro, Francesca (Antropologia Pubblica, 2024)
For anthropologists working in their own home country, the ethical dilemmas brought about by the relationship with the community they study are different – although not entirely "other" – compared to those that anthropologists working in so called “exotic” fields face (Tarabusi 2014). When the field is "at home" (Jackson 1987; Peirano 1998), the subjects who participated in the research «surround the anthropologist at her or his desk» (Mosse, 2006: 937), “they read what we write” (Brettell 1993), sometimes claiming the possibility to raise objections and challenging the ethnographer’s authority (Mosse 2006, 2015). Our stakeholders – whether the sponsors or the other informants and interlocutors – may also feel somehow "betrayed" by the ethnographic representation (Brettell 1993; Fabietti 1999; Scheper-Hughes 2001; Rossi 2003; Semi 2010); they cannot recognize themselves and their practices in the ethnographic account of their experience (Sorgoni 2011). Reactions to the anthropological writing can be extremely emotional: they, in fact, have to do with «the relationship between professionals [...] to descriptions of their organizational work» (Mosse 2015: 131). Publishing is, therefore, a particularly delicate moment in the relationship between the anthropologist and his interlocutors. Drawing on empirical experience, this paper describes the negative reactions to writing. The purpose is twofold: exploring the issue of ethical dilemmas involved in the negative reception of an ethnographic account; and outlining the possible strategies that allow limiting the risks that Applied and “at home” Anthropology entail.